High sink strength prevents photosynthetic down-regulation in cassava grown at elevated CO2 concentration - Ruiz-Vera, Ursula M (Journal of experimental botany, 2021)
© The Author(s) 2020. Published by Oxford University Press on behalf of the Society for Experimental Biology.